A comparative study of health outcomes between elderly Migrant and non-migrant population in India: Exploring health disparities through propensity score matching - Bittu Mandal; Kalandi Charan Pradhan (SSM-Popul. Health, 2024)
Migrants constitute a vulnerable segment of the population, particularly susceptible to various health challenges. Despite this, limited research has delved into the comparative health statuses of migrants and non-migrants in the rising elderly population. This study aims to bridge this gap by exploring health disparities between these two groups. Leveraging data from a nationally representative, large-scale Longitudinal Ageing Study in India (LASI) survey (n = 29002; 3103 Migrants and 25899 Non-migrants), this research focuses on four health indicators: selfrated health (SRH), depression, multimorbidity, and functional limitations. The study undertakes descriptive and bivariate analyses for migrant and non-migrant groups and employs propensity score matching techniques to fulfil its objectives. The findings reveal that for respective migrant and non-migrant populations, the prevalence of poor-SRH was 24.04 % and 16.29 %; depression was 12.32 % and 6.62 %; multimorbidity was 26.78 % and 15.71 %, and functional limitation was 28.35 % and 23.13 %. The study uncovers a 2.4 percentage point increase in poor self-rated health, a 1.0 percentage point rise in depression, and notably, a 4.2 and 1.0 percentage point elevation in multimorbidity and functional limitations among migrants relative to non-migrants. Evident from the outcomes is a stark health disparity, emphasising migrants' heightened vulnerability across multiple health dimensions. The implication of this research highlights the necessity for policy interventions aimed at eliminating health inequalities between migrant and non-migrant populations.
Keywords: Outpatient visit costs; Primary health care; Health facilities costs; Out-of-pocket expenditure; Government expenditure; Health financing; Public facilities; Private facilities